STUDYING NATIONAL MUSIC CLASSES OF SECONDARY SCHOOLS - Kasimjonova Marjona Alisher kizi (Journals Park Publishing, 2023)
This article provides detailed information about national pop songs, the formation of feelings of love for the art of national music by teaching national pop songs to students in music culture classes.
Keywords: national, national pop, music, culture, student, lesson, art, national value, tradition.